BY + complément dans les énoncés passifs anglais : une relation non-spatiale représentée spatialement - Yves-Bernard Malinier (Anglophonia)
By assumes a large array of meanings and there are semantic links between its superficially diverse uses. These include agency, cause, instrumentality, means, manner, etc.... Among this large array, the preposition is also used to head complements in long passive clauses.The purpose of this article is to show that the preposition may be given a locative interpretation when it is used to (re)introduce the noun phrase that corresponds to the grammatical subject of the active counterpart.The demoted Agent or Cause that activates a change of state can be viewed as an intermediate point (or L0Ci/o) on a path or route to an endpoint, i.e. the resultant state of the Patient or Experiencer.